Attenuation of primate aging via systemic infusion of senescence-resistant mesenchymal progenitor cells - Aisha Siddique; Ismail M. Shakir; Mo Li (Cell Regeneration, 2025)
Abstract Aging is characterized by progressive functional decline driven by stem cell exhaustion, chronic inflammation, and cellular senescence. Mesenchymal progenitor cells (MPCs), which play a central role in tissue repair, are particularly vulnerable to age-associated dysfunction. Lei et al. (Cell 188:1-22, 2025) address this limitation by engineering human embryonic stem cell-derived MPCs with enhanced FOXO3 activity (termed SRCs). Intravenous administration of FOXO3-SRCs to aged cynomolgus macaques significantly slowed aging across multiple organs compared to wild-type MPCs. SRC treatment improved cognitive performance, preserved brain structure, protected bone integrity, and rejuvenated immune function. Transcriptomic and DNA methylation aging clocks revealed substantial reductions in biological age, with the most pronounced rejuvenation observed in the reproductive system, skin, lung, muscle, and hippocampus. These effects were partly attributed to SRC-derived exosomes enriched in gero-protective proteins and metabolites. Importantly, SRCs exhibited robust safety, showing no tumorigenicity or immunogenicity. This work positions FOXO3-enhanced MPCs and their exosomes as promising candidates for systemic anti-aging interventions, shifting the therapeutic paradigm from treating individual diseases to targeting the aging process itself.